Perpetuation of Stemphylium blight of garlic under mid hill conditions of Himachal Pradesh - SUMAN KUMAR*, SHABNAM KATOCH and (Indian Phytopathology, 2017)
Blight of garlic caused by Stemphylium vesicarium is of common recurrence and is known to occur in almost all the garlic growing areas of India including Himachal Pradesh. In the present study, surveys during 2014 and 2015 were conducted to assess the pathogen associated and its mode of perpetuation. The morpho-cultural and pathological tests with fungal isolates taken from different areas indicated S. vesicarium to be the cause of garlic blight. The pathogen was invariably found to be soil borne in nature and seed borne to some extent. The sexual fruiting bodies (pseudothecia) of Pleospora alli were detected from garlic debris buried at different depths. Inoculation of healthy leaves with pseudothecia produced characteristic leaf spots that highlight the role of plant debris as a source of perpetuation.